2019
DOI: 10.1177/0023830919890068
|View full text |Cite
|
Sign up to set email alerts
|

Between Äh(m) and Euh(m): The Distribution and Realization of Filled Pauses in the Speech of German-French Simultaneous Bilinguals

Abstract: Filled pauses are well known for their speaker specificity, yet cross-linguistic research has also shown language-specific trends in their distribution and phonetic quality. To examine the extent to which speakers acquire filled pauses as language- or speaker-specific phenomena, this study investigates the use of filled pauses in the context of adult simultaneous bilinguals. Making use of both distributional and acoustic data, this study analyzed UH, consisting of only a vowel component, and UM, with a vowel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Third, regarding N-only FPs (exclusive to Spanish), there was not a significant difference between the two Spanish-speaking groups, indicating that the bilinguals, once again, display patterns like those of the Spanish comparisons. The findings based on RQ 1 support previous research showing that dimensions such as relative FP usage can vary across languages and dialects (e.g., Lo, 2019;Tian et al, 2017;Wieling et al, 2016)-here, we show that the same principles apply when comparing bilingual and representative comparison speakers.…”
Section: Answering the Research Questionssupporting
confidence: 89%
See 2 more Smart Citations
“…Third, regarding N-only FPs (exclusive to Spanish), there was not a significant difference between the two Spanish-speaking groups, indicating that the bilinguals, once again, display patterns like those of the Spanish comparisons. The findings based on RQ 1 support previous research showing that dimensions such as relative FP usage can vary across languages and dialects (e.g., Lo, 2019;Tian et al, 2017;Wieling et al, 2016)-here, we show that the same principles apply when comparing bilingual and representative comparison speakers.…”
Section: Answering the Research Questionssupporting
confidence: 89%
“…The situation of sustained, cross-generational contact between Afrikaans and Spanish is not, to our knowledge, replicated in any other region in the world. In our analysis, we have gone beyond the impressionistic description of FP usage in bilingual speech-our research represents an important step in obtaining an objective, acoustic analysis of bilingual data produced in a spontaneous setting (see also Erker & Bruso, 2017;Lo, 2019). Specifically, we focused on the relative use of three different types of FPs (categorical analysis), as well as on vowel quality and segmental durations (continuous analysis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is little acoustic evidence for this claim, because crosslinguistic studies examining filled pauses are rare. One study with 15 German-French simultaneous bilinguals showed that they developed language-specific filled pauses (Lo, 2019). In today's society, many speakers are sequential bilinguals.…”
Section: Introductionmentioning
confidence: 99%
“…in vowel quality, (Candea et al, 2005 ) and in segmental form/preference (Clark and FoxTree, 2002 )]. The use of FPs has been addressed in more recent studies on bilingualism (Gilquin, 2008 ; Rose and Watanabe, 2019 ; de Boer and Heeren, 2020 ; Lo, 2020 ; Muhlack, 2023 ) and is yet to be considered broadly in heritage language research (Polinsky, 2018 ). This gap will be addressed in this study.…”
Section: Introductionmentioning
confidence: 99%